2012
DOI: 10.1534/g3.111.001396
|View full text |Cite
|
Sign up to set email alerts
|

A Whole-Chromosome Analysis of Meiotic Recombination inDrosophila melanogaster

Abstract: Although traditional genetic assays have characterized the pattern of crossing over across the genome in Drosophila melanogaster, these assays could not precisely define the location of crossovers. Even less is known about the frequency and distribution of noncrossover gene conversion events. To assess the specific number and positions of both meiotic gene conversion and crossover events, we sequenced the genomes of male progeny from females heterozygous for 93,538 X chromosomal single-nucleotide and InDel pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 63 publications
7
73
4
Order By: Relevance
“…0.13, P , 0.006, all scales). We found no other previously reported motifs or short repeats associated with rates of crossing over in D. melanogaster or D. pseudoobscura (Cirulli et al 2007;Kulathinal et al 2008;Stevison and Noor 2010;Comeron et al 2012;Miller et al 2012), humans (Baudat et al 2010Myers et al 2010;Parvanov et al 2010), or dogs (Axelsson et al 2012) to be correlated with recombination rates at multiple window sizes.…”
Section: Sequence Motifscontrasting
confidence: 74%
See 2 more Smart Citations
“…0.13, P , 0.006, all scales). We found no other previously reported motifs or short repeats associated with rates of crossing over in D. melanogaster or D. pseudoobscura (Cirulli et al 2007;Kulathinal et al 2008;Stevison and Noor 2010;Comeron et al 2012;Miller et al 2012), humans (Baudat et al 2010Myers et al 2010;Parvanov et al 2010), or dogs (Axelsson et al 2012) to be correlated with recombination rates at multiple window sizes.…”
Section: Sequence Motifscontrasting
confidence: 74%
“…These authors also noted that poly(A) stretches are associated with crossover events in yeast (Mancera et al 2008), and the dinucleotide CA repeat stimulates homologous recombination in human cells in culture (Wahls et al 1990). In addition, we find significant correlations between motif incidence and recombination rate for the motif AAAC [CG] AAA, a core of a previously identified motif in D. melanogaster (Comeron et al 2012), as well as the motif ATG-GAAA, which has also been previously implicated with crossover distribution in D. melanogaster (Miller et al 2012). The former is correlated with recombination rates at the 5-, 10-, and 20-kb scales (r .…”
Section: Sequence Motifsmentioning
confidence: 56%
See 1 more Smart Citation
“…A nonrandom distribution of biased gene conversion (Nagylaki 1983a(Nagylaki , 1983bMarais 2003) could potentially generate these correlated patterns of reduced polymorphism. Note that the length of gene conversion tracks in Drosophila (several 810 [Hilliker et al 1994;Comeron et al 2012;Miller et al 2012]) is roughly the physical scale of our study. However, the definitive evidence for the significant role of biased gene conversion in Drosophila is still lacking.…”
Section: Discussionmentioning
confidence: 70%
“…Second, our conclusion that mean conversion-tract lengths are typically on the order of one to several kilobases is also consistent with previous observations. Estimates of L are on the order of 400 bp in Eubacteria (Santoyo and Romero 2005), in the range 500-4000 bp in S. cerevisiae (Ahn and Livingston 1986;Judd and Petes 1988;McGill et al 1990), and 400-1400 bp in D. melanogaster (Hilliker et al 1994;Preston and Engels 1996;Miller et al 2012). Paigen et al (2008) have observed conversion-tract lengths in the mouse ranging from 200 to 1200 bp, and Padhukasahasram and Rannala (2013) have inferred tract lengths of 100-900 bp on human chromosomes.…”
Section: Discussionmentioning
confidence: 99%